Efectividad de la intervención de enfermería para mejorar la atención y la calidad de vida en los pacientes oncológicos - Lluén Pisfil, Sonia del Pilar (2019)
Objective: Systematize the evidence of the effectiveness in the intervention of nursery to offers a better attention and a better quality of life to the oncology patients. Material and Methods: Systematic inspection quantitative type, subdued by a critical selection, using the Grade’s systems for the identification of the evidences founded of the grade on the next database: Pubmed, Sciencedirect, Cochrane, all of it respond to the quantitative type and the designs of the study systematic inspection, goal- analysis, cohort study. According to the study obtained the systematic inspection on the present study, showed of the 10 academical research examined systematically the 50% (n= 5/10) is systematic inspection, the 40% (4/10) is cohort study and the 10% (1/10) is goal- analysis. According to the results obtained from the systematic inspection made on the present study, come from the countries like Spain (30%), Belgium (10%), USA (10%), Chile (10%), China (10%), Germany (10%), Cuba (10%) and Colombia (10%). Results: As well, the evidences founded the 100% (n= 10/10) point at the effectiveness in the intervention of nursery to offers a better attention and a better quality of life to the oncology patients. Conclusion: The effectiveness in the intervention of nursery offers a better attention and a better quality of life. The interventions offered by the nurse in the most of the cases managed an improvement on the patient with cancer and in the knowledge of the family.